2001
DOI: 10.1590/s1516-89132001000100006
|View full text |Cite
|
Sign up to set email alerts
|

Compression induced intercellular shaping for some geometric cellular lattices

Abstract: The wall perimeter fraction, which contact neighboring cells, was named compression ratio (α). A zero compression ratio indicates maximum intercellular (air) volume (v G , v/v)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…4), it can be observed that readings by these two methods were proportional with slopes of 1.16 for lettuce, 1.13 for kale, and 1.04 for chicory. These values are consistent with the fact that the flattening method conceptually should generate pressure readings smaller than the cell turgor pressure measured with the pressure probe, except for limiting tissues in which the cell wall thickness and the intercellular air volumes could be considered vanishingly small (Calbo and Nery, 2001). The percentage of intercellular air volume (v/v) in the leaf is expressive and for most crops it is in the range between 20% and 30% (Spector, 1956).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…4), it can be observed that readings by these two methods were proportional with slopes of 1.16 for lettuce, 1.13 for kale, and 1.04 for chicory. These values are consistent with the fact that the flattening method conceptually should generate pressure readings smaller than the cell turgor pressure measured with the pressure probe, except for limiting tissues in which the cell wall thickness and the intercellular air volumes could be considered vanishingly small (Calbo and Nery, 2001). The percentage of intercellular air volume (v/v) in the leaf is expressive and for most crops it is in the range between 20% and 30% (Spector, 1956).…”
Section: Resultssupporting
confidence: 80%
“…Using a more general plant physiology reasoning, the flattening procedure was extended to estimate cell turgor pressure of other convex fruits and vegetables covered by soft dermal tissues composed of thin-walled poliedric cells that cover the internal plant cellular structure made out of parenchymatous cells having deformable intercellular air volumes. Accordingly, for some regular cellular lattices, it was demonstrated that there is a simple mathematical relation between the flattening pressure and cell turgor (Calbo and Nery, 2001). In these lattice models, the flattening pressure and the cell turgor pressure are related by a cell compression ratio, whose magnitude ranges from zero to one depending on remaining intercellular air volume fraction during mechanical axial compression assays.…”
mentioning
confidence: 99%
“…In this regard, it is important to mention that theoretical estimations (as in Calbo & nery, 2001) of such phenomena (Calbo et al, 2010) that use flattening pressure, as in older articles, are always slightly smaller than the average cell turgor pressure measured with a cell pressure probe. Therefore, a Wiltmeter instrument measures an average pressure of a leaf as a whole organ.…”
Section: Resultsmentioning
confidence: 98%
“…Such density error may not be too high if water loss is below 25% and if the intercellular air volume fraction can be considered stable. According to Calbo and nery (2001) with pressure probe measurements, Calbo et al (2010) observed linear relationships, with a decline close to one, when these methods were applied to detached leaves of lettuce (Lactuca sativa L.), kale (Brassica oleracea L. var. acephala), and chicory (Chichorium endivia L.) subjected to air dehydration.…”
Section: *R = (M -M S )/(M I -M W -M S )mentioning
confidence: 99%
“…After placing the applanating plate on the top of a fruit, the user waits 1 or 2 minutes to read flattened area at presumed constant cell pressure. Alternatively, these systems allow immediate flattened area readings at presumed constant cell volume [70] to calculate firmness as a ratio between the applied external force and the fruit flattened area.…”
Section: Related Workmentioning
confidence: 99%